Theatre and its other : Abhinavagupta on dance and dramatic acting - Ganser, Elisa (Gonda indological studies, 2021)
"What is Dance? What is Theatre? What is the boundary between enacting a character and narrating a story? When does movement become tinted with meaning? And when does beauty shine alone as if with no object? These universal aesthetic questions find a theoretically vibrant and historically informed set of replies in the oeuvre of the eleventh-century Kashmirian author Abhinavagupta. The present book offers the first critical edition, translation, and study of a crucial and lesser known passage of his commentary on the Nāṭyaśāstra, the seminal work of Sanskrit dramaturgy. The nature of dramatic acting and the mimetic power of dance, emotions, and beauty all play a role in Abhinavagupta's thorough investigation of performance aesthetics, now presented to the modern reader"--